2019
DOI: 10.1002/per.2197
|View full text |Cite
|
Sign up to set email alerts
|

Resting Frontal Eeg Asymmetry and Personality Traits: A Meta–Analysis

Abstract: Frontal asymmetry has been widely used as a marker of emotion, motivation, and psychopathology. When assessed during the resting state, it is regarded as an index of trait approach and withdrawal motivation. However, the replicability of these associations with personality is currently unclear. The present meta-analysis seeks to provide a comprehensive quantitative review of the relationship between personality traits and resting electroencephalographic (EEG) frontal asymmetry. We distinguished five personalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 149 publications
(233 reference statements)
4
39
3
Order By: Relevance
“…Increases in left frontal alpha asymmetry have consistently been found to be a reliable biomarker of approach‐motivated anger (d'Alfonso, van Honk, Hermans, Postma, & de Haan, 2000; Harmon‐Jones & Gable, 2018; Jensen‐Campbell et al, 2007; Kelley, Eastwick, Harmon‐Jones, & Schmeichel, 2015; Verona et al, 2009). However, a recent meta‐analysis found small effect sizes for the relationship between frontal asymmetry and anger (Kuper, Käckenmester, & Wacker, 2019), suggesting that the relationship between frontal asymmetry and anger may not exist across all contexts for all individuals. For example, when anger is not able to be expressed, some individuals do not show a relationship between left frontal alpha asymmetry and anger (Zinner, Brodish, Devine, & Harmon‐Jones, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Increases in left frontal alpha asymmetry have consistently been found to be a reliable biomarker of approach‐motivated anger (d'Alfonso, van Honk, Hermans, Postma, & de Haan, 2000; Harmon‐Jones & Gable, 2018; Jensen‐Campbell et al, 2007; Kelley, Eastwick, Harmon‐Jones, & Schmeichel, 2015; Verona et al, 2009). However, a recent meta‐analysis found small effect sizes for the relationship between frontal asymmetry and anger (Kuper, Käckenmester, & Wacker, 2019), suggesting that the relationship between frontal asymmetry and anger may not exist across all contexts for all individuals. For example, when anger is not able to be expressed, some individuals do not show a relationship between left frontal alpha asymmetry and anger (Zinner, Brodish, Devine, & Harmon‐Jones, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Others have similarly found that, in both healthy and depressed participants, symptoms of depression associated with low motivation (which typically load on the low pole of Extraversion) were associated with decreased relative left frontal cortical activity, but only during reward anticipation (Nelson, Kessel, Klein, & Shankman, 2018). In contrast, recent meta-analyses have repeatedly found that Extraversion is unrelated to left frontal asymmetry at rest (Kuper, Käckenmester, & Wacker, 2019;Wacker, Chavanon, & Stemmler, 2010).…”
Section: Let Theory Be Your Guide: How Detailed Explanations Of Bmentioning
confidence: 99%
“…Thus, brain alpha oscillations can be considered as the measure of latent individual disposition to a specific style of behavior. However, the replicability of these associations with approach/avoidance personality traits is still unclear [7]. The same can be 1.…”
Section: Introductionmentioning
confidence: 99%